Effects of climate and corrosion on concrete behaviour - Ismail, Mohamed; Egba, E. (2017)
© 2017 Author(s). Corrosion of steel is a damaging agent that reduces the functional and structural responsibilities of reinforced concrete structures. Accordingly, reinforced concrete members in the environments that are prone to concrete carbonation or chloride attack coupled with high temperature and relative humidity suffer from accelerated corrosion of reinforcing material. Also, literature proves that climate influences corrosion of concrete, and suggests investigation of impact of corrosion on concrete based on climate zone. Therefore, this paper presents the effects of climate and corrosion on concrete behavior, using bond strength of concrete as a case study. Concrete specimens were prepared form concrete mix that was infested with 3.5 kgm-3 of sodium chloride to accelerate corrosion. The specimens were cured sodium chloride solution 3.5% by weight of water for 28 days before placing them in the exposure conditions. Pull-out tests were conducted at time intervals for one year to measure the impact of exposure condition and corrosion on bond strength of concrete. The results show reduction of bond strength of concrete by 32%, 28% and 8% after one year of subjection of the specimens to the unsheltered natural climate, sheltered natural climate, and laboratory ambient environment respectively. The findings indicate that the climate influences corrosion, which reduces the interlocking bond between the reinforcing bar and the adjacent concrete.